DETERMINANT OF TOTAL ASSETS OF SHARIA BANKS IN INDONESIA (An Error Correction Model Approach) - Ayif fathurrahman; Maya Kumala Sari (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
This study aims to analyze the factors that affect the total assets of Islamic banks in Indonesia in 2015: 1 - 2018: 9. The data used include Third Party Funds, Financing to Deposit Ratio (FDR), Third Party Funds (TPF), Gross Domestic Product (GDP), Sharia Bank Total Assets. This study uses the Error Correction Model (ECM) approach. The study result show that both  long-term and short-term Third Party Funds (TPF) and Financing to Deposit Ratio ( FDR) have a positive and significant relationship to the total assets of Islamic banks in Indonesia. At the same time, inflation and Gross Domestic Product (GDP) have a positive and not significant effect on the total assets of Islamic banks in Indonesia. The result shows that internal factors significantly affect the total assets of Islamic banks in Indonesia. In contrast, external factors do not have a significant effect on the total assets of Islamic banks.